Expression pattern and clinicopathologic significance of NKD1 in human primary hepatocellular carcinoma. Issue 4 (23rd February 2015) - Zhang, Sheng; Li, Jie; Yin, Zhen‐Yu; Liu, Ping‐Guo; Zhao, Wen‐Xiu; Xie, Cheng‐Rong; Zhao, Bi‐Xin; Wang, Xiao‐Min
Abstract : It has been reported that NKD1 was an antagonist of the canonical Wnt/β‐catenin pathway. While there is little information regarding NKD1 expression pattern in human hepatocellular carcinoma (HCC). The aim of this study was to investigate the clinicopathologic significance and expression pattern of NKD1 in HCC. NKD1 protein expressions in 69 paired HCC cancer/adjacent non‐cancerous tissues were detected by Western blot. Immunohistochemical studies were performed on 58 cases of HCC with integrated clinical information. NKD1 protein expression was divided into normal and low expression group and correlations between NKD1 protein expression and clinicopathologic factors were then evaluated. Western blot results showed that NKD1 protein levels were significantly lower in cancerous tissues compared with corresponding normal tissue (p < 0.05). In addition, we found that the level of NKD1 protein expression in HCC was significantly associated with tumor size (p = 0.011), intra or extra‐hepatic metastasis (p = 0.010) and differentiation (p = 0.003). This is to our knowledge the first report investigating NKD1 protein expression pattern in HCC. Our data show that decreased NKD1 protein expression is associated with clinicopathologic factors, and suggest that NKD1 may play an important role in the development of HCC and could serve as a novel biomarker for HCC after further investigation.